Theoretical Electronic Circular Dichroism Study of 1, 3‐Diene Derivatives for the Elucidation of ECD Spectra of 1, 3‐Cyclohexadiene and Its Derivatives. Issue 8 (18th May 2015) - Nakayama, Naofumi; Goto, Hitoshi
Abstract The origin of P‐ or M‐chirality of methyl substituted 1, 3‐cyclohexadienes are elucidated by time‐dependent density functional theory (TD‐DFT) calculation of 1, 3‐cyclohexadiene derivatives and acyclic 1, 3‐dienes. The sign‐inversion of the rotatory strength of the lowest excited state between 1, 3‐cyclohexadiene and (5R)‐axial‐methyl‐1, 3‐cyclohexadiene is caused by the conformation around the (C=)C‐C(‐Me) dihedral angle. The correlation between the sign of the rotatory strength and conformation has been found not only in methyl substituted derivatives but also fluoro substituted compounds. Chirality 27:476–478, 2015. © 2015 Wiley Periodicals, Inc.